Nurses' Cancer Pain Management Competence Scale: Turkish Validity and Reliability Study - Bahcecioglu-Turan, Gulcan; Yavuzer-Bayrak, Nisa; Basak, Seda; Yilmaz-Karabulutlu, Elanur (Elsevier Science Inc, 2025)
Aim: The aim of this study was to adapt the Nurses' Cancer Pain Management Competency Scale into Turkish and to examine the validity and reliability of the scale. Methods: This methodological study was conducted with 244 nurses who were working in Turkey between July 2023 and May 2024. Data were collected online by using Personal Information Form and Nurses' Cancer Pain Management Competency Scale (NCPMCS). In the analysis of the data, Cronbach's alpha, Kaiser Meyer Olkin (KMO) and Barlet's sphericity test, fit indices, Average variance extracted (AVE) and Composite reliability (CR) were assessed. Maximum shared squared variance (MSV) and Average shared squared variance (ASV) were evaluated for divergent validity. Results: The factor loadings of the scale items were found to vary between 0.740 and 0.970. The fit indices of the scale were found as follows: X-2 = 170.38, df = 69 (p < .05), X-2/df = 2.49, RMSEA = 0.078, CFI = 0.97, RMR = 0.027, SRMR = 0.043 and TLI = 0.96. The Cronbach's alpha values of the scale sub-dimensions ranged between 0.888 and 0.931 and the overall Cronbach's alpha coefficient was 0.828. The validity of the Turkish version of Nurses' Cancer Pain Management Competency Scale was established without any changes in the original scale form. Conclusion: Nurses Cancer Pain Management Competency Scale Turkish form is a valid and reliable measurement tool to evaluate the competencies of nurses in cancer pain management and to be used in clinical practice. (c) 2025 American Society for Pain Management Nursing. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Validity; Reliability; Nurse; Cancer pain